2019
DOI: 10.3390/medicina55050157
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Status and Cardiometabolic Risk Factors in Institutionalized Adults with Cerebral Palsy

Abstract: Background and Objectives: Cerebral palsy (CP) is a set of permanent disorders that limit physical activity and increase the risk of developing other diseases, such as metabolic syndrome (MS). Adequate nutrition can contribute to the prevention of associated symptoms. The main objective of this study is to evaluate the nutritional status and the prevalence of cardiometabolic risk factors in adults with CP and Gross Motor Function Classification System (GMFCS) levels between IV and V. Materials and Methods: A s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(25 citation statements)
references
References 45 publications
0
21
0
Order By: Relevance
“…They were visual-spatial organization skills, semantic memory, BMI, diastolic BP, and resting heart rate. Notably, cognitive impairment has been shown to be prevalent as individuals with CP progress into adulthood [ 25 , 26 ]. Furthermore, we previously showed that metabolic syndrome is a prominent clinical characteristic of CP [ 8 , 14 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…They were visual-spatial organization skills, semantic memory, BMI, diastolic BP, and resting heart rate. Notably, cognitive impairment has been shown to be prevalent as individuals with CP progress into adulthood [ 25 , 26 ]. Furthermore, we previously showed that metabolic syndrome is a prominent clinical characteristic of CP [ 8 , 14 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…While both over-and underweight issues have been reported in children and adults with CP, few studies have looked at actual nutritional intake and quality. 12 Better nutritional intake is thought to play a role in enhanced survival in the most severely involved children with CP. Other studies, however, have found overweight issues beginning in adolescence and even younger children with CP.…”
mentioning
confidence: 99%
“…As hypothesized, adults with CP and malnutrition fare more poorly when they are hospitalized. One small Spanish study showed a strong correlation between the severity of CP, measured by GMFCS levels, and the prevalence of malnutrition 24 . In our larger US national study, malnutrition was recognized and coded as a secondary diagnosis in >1 of every 8 hospitalized adult patients with CP.…”
Section: Discussionmentioning
confidence: 65%
“…One small Spanish study showed a strong correlation between the severity of CP, measured by GMFCS levels, and the prevalence of malnutrition. 24 In our larger US national study, malnutrition was recognized and coded as a secondary diagnosis in >1 of every 8 hospitalized adult patients with CP. Prevention, recognition, and treatment of malnutrition among populations with disabilities should be a public health priority, given the need to reduce disparities and inequities.…”
Section: Discussionmentioning
confidence: 99%